Predictive value of serum βHCG level in ectopic pregnancy: A cross sectional study - Mandana Mansour Ghanaie; Sanaz Hoshyarmanesh; Seyedeh Maryam Asgari; Seyed Mohammad Asgari Galebin; Fereshteh Fakor (Health Science Reports, 2023)
Abstract Background and Aims Ectopic pregnancy (EP) is a potentially life‐threatening emergency. We investigate the predictive value of serum βHCG level and it's changes from the baseline to the 4th and 7th days after single dose (SD) methotrexate (MTX) treatment in successful treatment of tubal EP. It is important for early diagnosis of EP. Methods In this cross‐sectional study, 690 women with tubal EP and under treatment with SD MTX were evaluated. Successful and failed groups were analyzed on the baseline, 4th and 7th days of MTX treatment. Data were analyzed using SPSS22 software. All p values of less than 0/05 were considered satistically significant. Results SD MTX treatment was successful in 584 (84.7%) patients. The mean baseline ßHCG value was 882.35 ± 430.76 in the successful group and 1083.99 ± 1080.25 in the failed group. There was a 19.53% decrease in ßHCG values between the baseline and 4th days in the successful group and a 12.94% increase in the failed group (p < 0.001). On days baseline, 4 and 7; receiver operating characteristic curve analysis's value was 504.5, 429, 279 for cut off; 58%, 73%, 81% for sensitivity and 51%, 52%, 55% for specificity, respectively. Conclusion A decrease in the ßHCG value and/or a cut‐off decrease of 59.9% on the baseline, 4th day and 81.6% between the baseline and 7th days, can predict the successful treatment of tubal EP with SD MTX.